Analyzing The Cellular and Genetic Alterations That Contribute to The Metastatic Spread of Malignant Tumors - Shamim, Rakhshanda; Waqar, Zaid; Haidar, Adeel; Niazi, Ammar; Sadiq, Muhammad Mustafa; Anam Ali, Bushra (Journal of Neonatal Surgery, 2025)
Background: The number one cause of cancer-related deaths across the globe is metastatic spread of malignant tumors. To determine therapeutic targets, it is important to understand cellular and genetic changes that facilitate invasion, dissemination, and colonization. Although this field can be improved through genomics, the interactions between tumor-intrinsic alterations and the microenvironment are not fully outlined, and thus, current metastasis-preventive approaches are limited. Objective: The purpose of the study was to examine cellular changes and genetic mutations related to tumor metastasis, to examine individual patient features, and to examine clinical correlations that point to possible areas of therapeutic intervention. Study Design: A retrospective observational study. Place and Duration of study: Pakistan Institute of Medical Sciences, PIMS, Islamabad, Pakistan. Jan 2024 to December 2024 Methods: Review of 100 patients with histologically proven malignant tumors was a retrospective observational study. Institutional records were used to collect demographic and clinical data. Recurrent mutations in TP53, KRAS, and PIK3CA of tumor tissue samples and epithelial-mesenchymal transition markers were assessed by immunohistochemistry. Statistical analyses comprised descriptive statistics, calculation of mean ages and standard deviation and comparison of groups using Student t-test with a significance level set to p < 0.05. Results: 100 patients (52 males and 48 females) were used as the cohort. The mean age was 59.4 years +- 11.2 SD. Genomic findings identified TP53 mutations in 45 percent of patients, KRAS mutations in 28 percent and PIK3CA mutations in 18 percent. Loss of E-cadherin expression was also found in 36 percent of samples and was associated with greater invasiveness. Analysis of the metastatic burden revealed that patients who had both TP53 and KRAS mutations had a much greater metastatic burden than patients without (p = 0.018). Clinical associations suggested that genetic changes and epithelial-mesenchymal transition signatures operated as a combined effect on progression, which underscored a suggestion that molecular heterogeneity is the basis of metastatic potential. Conclusion: We have shown that genetic mutations, together with cellular reprogramming (epithelial-mesenchymal transition) contribute to metastasis. Combined TP53 and KRAS mutations and their relationship with metastatic progression are correlated, which is important to identify potential risk stratification biomarkers. The combination of molecular and cellular analysis provides informative tools to develop therapies that will help intercept metastatic progression, which ultimately will raise the prognosis and survival rates in patients with progressive malignant tumors.